Infantile Tremor Syndrome: A Case Report - Inamdar, Syed Zia; P, Purnagopinath; Kumari, Vijaya; Nandikol, Sunanda; Londe, Sushilkumar; Kulkarni, Raghavendra; Patil, Mallanagouda (Journal of Pharmacy Practice and Community Medicine)
Infantile Tremor Syndrome is a clinical state, characterized by anemia, skin depigmentation, tremors and developmental delay in children between age 5 months to 3 years. Nutritional deficiency is one of the most accepted theories, usually seen among breastfeeding vegetarian mothers. The present case report describes demographic, clinical, laboratory profile and treatment outcome of infantile tremor syndrome diagnosed in a 5 month old female child admitted to the pediatric ward of tertiary care hospital.
Keywords: Infantile tremor syndrome; Nutrition; Vegetarian; Tremors; VitaminB12 deficiency; Pediatric